1978
DOI: 10.1002/1097-0142(197812)42:6<2613::aid-cncr2820420617>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Specific immunotherapy of established visceral micrometastases by BCG-tumor cell vaccine alone or as an adjunct to surgery

Abstract: A vaccine of Bacillus Calmette-Guérin (BCG) admixed with tumor cells induced systemic immunity and had a therapeutic effect on subclinical, disseminated micrometastases. Inbred strain 2 guinea pigs given intravenous injections of either 10(4), 10(5) or 10(6) syngeneic L10 hepatocarcinoma cells were vaccinated after metastatic foci were established in the lung parenchyma. The studies demonstrate that under defined conditions of vaccine preparation and regimen, nontumorigenic preparations of BCG and tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…These discrepancies might suggest a lesser significance of innate immunity in the anti-cancer response, but might also be connected to different types of tumors and of BCG, used in clinical studies. Mouse studies (19), as well as clinical observations in patients with bladder cancer confirmed the different therapeutic potential of BCG strains (20).…”
Section: Discussionmentioning
confidence: 83%
“…These discrepancies might suggest a lesser significance of innate immunity in the anti-cancer response, but might also be connected to different types of tumors and of BCG, used in clinical studies. Mouse studies (19), as well as clinical observations in patients with bladder cancer confirmed the different therapeutic potential of BCG strains (20).…”
Section: Discussionmentioning
confidence: 83%
“…The guinea-pig hepatoma model (31)(32)(33) involved the use of hepatoma induced in a strain of guinea pigs by injection of dimethylnitrosamine. The hepatoma was then converted into an ascites tumor.…”
Section: Lymphatic Metastasismentioning
confidence: 99%
“…In other studies tumor cells have been injected directly into lymphatic channels (168,169). Experiments using these models have provided useful information on the mechanism by which (174), the diversity of the morphologic and immunologic changes occurring in lymph nodes containing tumor burdens of increasing severity (189) and the efficacy of chemotherapeutic (165,184,185) and immunotherapeutic protocols (172,188) in treating established lymph node metastases. We remain ignorant, however, about many important features of lymph node function in metastasis.…”
Section: Models Of Lymphatic Metastasismentioning
confidence: 99%